Diagnostic imaging of the chest - Wormanns, Dag (Thieme, 2020)
"Due to the remarkable concentration of various vital organs that can be visualized in thoracic imaging, the region occupies a firm central place in the spectrum of diagnostic imaging. The book is based on the contents of the curriculum for thoracic imaging of the European Society of Radiology and covers the gamut of issues in thoracic imaging that radiologists are faced with in their daily clinical practice. Contents are divided into four main sections: fundamentals of diagnostic thoracic imaging, diseases of the chest and special findings, differential diagnostic considerations and incidental findings, and glossary. Key Features: Full coverage of all disease entities as they affect the lungs, airways, pleura, mediastinum, thorax wall and diaphragm, thoracic arteries and veins, and the heart All imaging modalities are covered in detail: projection radiography, fluoroscopy, ultrasound, CT, and MRI, as well as digital image postprocessing Subsections concentrate on the more critical findings, such as pulmonary nodules and cavitary lesions Special section on occupational pulmonary diseases Congenital malformations of the thorax, and much more Diagnostic Imaging of the Chest is an essential reference guide for radiologists, both in training and in practice"--